Case report: a giant cell-rich gnathic bone lesion in a child with pycnodysostosis - Spencer, C.; Makka, A.; Singh, S.; McGuire, J.; Washaya, N.; Hein, G.; Zampoli, M.; Fieggen, K. (Frontiers in Oral Health, 2023)
Pycnodysostosis is a skeletal dysplasia characterised by short stature, generalized osteosclerosis, acro-osteolysis, and recognizable facial features. Oral manifestations are commonly described and include a high arched palate with dental crowding and malocclusion, hypoplastic enamel and retained deciduous teeth with impacted permanent teeth, and there is an increased risk of developing osteomyelitis of the jaw. We report here the history of a nine-year-old male with the typical facial and skeletal phenotype of pycnodysostosis, but novel oral features. He presented with bilateral progressive facial swelling which caused functional impairment with chewing as well as contributed to his severe obstructive sleep apnea (OSA). The severity of his OSA required surgical intervention and the lesions were resected. Extensive bone remodelling and replacement by fibrous tissue was noted on submucosal dissection and bilateral subtotal maxillectomies were required. The histopathology of the biopsied lesion was consistent with a giant cell-rich lesion. Genetic testing identified a pathogenic homozygous variant in the CTSK gene, c.953G>A, pCys318Tyr. The proband had a good post-surgical response with sustained improvement in his sleep OSA. We present here the history and clinical characteristics of a patient with typical features of pycnodysostosis and an unusual presentation and histopathology of gnathic bone lesions. This report adds to the body of literature on this rare condition and also highlights the finding of giant cell-rich lesions of the gnathic bones. Giant cell-rich lesions in pycnodysostosis have previously been reported in two cases in the literature. While there is not enough evidence to support a certain association with pycnodysostosis, it is prudent to consider regular oral dental reviews in affected individuals to identify pathology early and avoid such life-threatening complications.